The Role of Character Education in Shaping The Personality of Generation Z Students - Andayanie, Lukie Masayu; Hartanto, Sigit; Sutama, S (Proceedings International Conference on Education Innovation and Social Science, 2025)
The digital era has given rise to Generation Z, a cohort characterized by high technological dependency, rapid information access, and a tendency toward individualism. These traits pose significant challenges in the development of student personality. This study aims to analyze the role of character education in shaping the personality of Generation Z students, to identify supporting and inhibiting factors in its implementation, and to evaluate the effectiveness of character education strategies applied in schools. A descriptive qualitative approach was employed, using interviews, observations, and documentation as data collection techniques. The findings indicate that character education plays a vital role in fostering students' values of integrity, empathy, and social responsibility. Key supporting factors include teacher role modeling, a school culture of character, and parental involvement, while the main obstacles are the negative influence of social media, lack of environmental supervision, and limited digital infrastructure. Effective strategies identified include the habituation of character values in daily school life, reinforcement through extracurricular activities, and integration of the Pancasila Student Profile program. These findings affirm that contextual and sustainable character education can positively and adaptively shape the personality of Generation Z students in the face of rapid societal change.